Designing Efficient Processes for Sustainable Bioethanol and Bio-Hydrogen Production from Grass Lawn Waste - Georgia Antonopoulou (Molecules, 2020)
The effect of thermal, acid and alkali pretreatment methods on biological hydrogen (BHP) and bioethanol production (BP) from grass lawn (GL) waste was investigated, under different process schemes. BHP from the whole pretreatment slurry of GL was performed through mixed microbial cultures in simultaneous saccharification and fermentation (SSF) mode, while BP was carried out through the C5yeast Pichia stipitis, in SSF mode. From these experiments, the best pretreatment conditions were determined and the efficiencies for each process were assessed and compared, when using either the whole pretreatment slurry or the separated fractions (solid and liquid), the separate hydrolysis and fermentation (SHF) or SSF mode, and especially for BP, the use of other yeasts such as Pachysolen tannophilus or Saccharomyces cerevisiae. The experimental results showed that pretreatment with 10 gH2SO4/100 g total solids (TS) was the optimum for both BHP and BP. Separation of solid and liquid pretreated fractions led to the highest BHP (270.1 mL H2/g TS, corresponding to 3.4 MJ/kg TS) and also BP (108.8 mg ethanol/g TS, corresponding to 2.9 MJ/kg TS) yields. The latter was achieved by using P. stipitis for the fermentation of the hydrolysate and S. serevisiae for the solid fraction fermentation, at SSF.